Determinan Penentu Earning Management dengan Growth Sales Sebagai Variabel Pemoderasi pada Perusahaan Consumer Goods di BEI - Picauly, Lydia; Sitohang, Santi Aji (Journal of Accounting and Management Innovation, 2018)
This study aims to test and analyze (1) Effect of Financial Performance (CR, ROA, DAR and TATO) partially to Earning Management. (2) The Influence of Financial Performance (CR, ROA, And DAR, TATO) collectively to Earning Management. (3) Whether Growth Sales can moderate the relationship between Financial Performance (CR, ROA, DAR and TATO) with Earning Management. The objective of this study is all consumer goods companies listed on the Indonesia Stock Exchange in 2013-2015 as many as 37 companies. The sample was chosen using survey method with 27 companies. Source of data comes from www.idx.co.id. The analysis method used is multiple linear regression analysis and residual test. The results indicate that (1) Together variables (CR, ROA, DAR and TATO) have significant effect on Earning Management (2) Partially (a) CR and DAR variables have positive influence on Earning Management (b) Negative and significant to Earning Management. (C) TATO variable has no significant effect on Earning Management. (3) Growth Sales is not a moderating variable so it cannot strengthen or weaken the relationship between variables (CR, ROA, DAR and TATO) with Earning Management. (4) Determinant of Earning Management is variable of Current Ratio, Return On Asset and Debt to Asset Ratio Key Words : Current Ratio, Return On Asset, Debt to Asset Ratio, Total Asset Turnover, Earning Management, Growth Sales